2008
DOI: 10.1111/j.1365-2699.2007.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Cycads in the insular South‐west Pacific: dispersal or vicariance?

Abstract: Aim Cycads constitute an ancient plant group that is generally believed to disperse poorly. However, one group of cycads (subsection Rumphiae) is thought to have dispersed relatively recently from a Malesian source area westwards to East Africa and eastwards into the Pacific, using a floatation-facilitating layer in their seeds. We use morphological and allozyme characters to investigate the relationships among the species within this group and to deduce whether the wide distribution was achieved by recent dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…The complex geological history of the Pacific, particularly in the Southwest, means that this issue has not been conclusively resolved for this region. Keppel et al (2008) showed that genetic similarity in a broadly distributed group of SWP cycads (subsection Rumphiae) revealed a likely recent oceanic dispersal rather than vicariance. In contrast, Heads (2008) presented vicariance arguments for a number of patterns that were previously thought to comprise 'dispersal' examples, including the Australia/Pacific Lotus australis complex, focused around New Caledonia and the SWP.…”
Section: Pacific Biogeographymentioning
confidence: 99%
“…The complex geological history of the Pacific, particularly in the Southwest, means that this issue has not been conclusively resolved for this region. Keppel et al (2008) showed that genetic similarity in a broadly distributed group of SWP cycads (subsection Rumphiae) revealed a likely recent oceanic dispersal rather than vicariance. In contrast, Heads (2008) presented vicariance arguments for a number of patterns that were previously thought to comprise 'dispersal' examples, including the Australia/Pacific Lotus australis complex, focused around New Caledonia and the SWP.…”
Section: Pacific Biogeographymentioning
confidence: 99%
“…This is an additional but essential justification for the present study to re-investigate the biogeography of the genus Cycas. Indeed, the biogeography of the genus Cycas has been investigated in recent studies (e.g., Keppel et al, 2008;Xiao and Möller, 2015). In their study, Xiao and Möller (2015) indicated, with high level of confidence (∼94%), that South China is the origin of the genus.…”
Section: Diversification and Historical Biogeographymentioning
confidence: 99%
“…In Asia, the genus is distributed across the Red River Fault between South China and the Indochina block, with Red River potentially constituting a geographical barrier for gene flow (Xiao and Möller, 2015). If this barrier was effective, we would expect to detect the signature of vicariance events in the evolutionary history of the genus Cycas (Keppel et al, 2008;Xiao and Möller, 2015). Then, the widespread distribution of Cycas from Asia to Africa, Australia and across the Pacific regions might have been mediated through long distance dispersal events across the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the conifer genus Agathis, often cited in support of the vicariance origin of Pacific island biotas (Whitmore, 1969;de Laubenfels, 1996), was found to have recently speciated in the Pacific, with the likely source being New Caledonia (Setoguchi et al, 1998). Similarly, Pacific cycads (genus Cycas) appear to have recently expanded their distribution following the evolution of adaptations that facilitate oceanic dispersal (Hill, 1996;Keppel et al, 2008). In addition, LDD and recent divergence are now known to have played a major role in determining the current distribution of Nothofagus Cook & Crisp, 2005a;Knapp et al, 2005), long considered to support vicariance scenarios (Linder & Crisp, 1995;).…”
Section: The Atlantis Theory (Vicariance)mentioning
confidence: 99%